Immunotherapy in Type 1 Diabetes: Emerging Therapies and Future Directions - Simran Thakkar; Saptarshi Bhattacharya; Lakshmi Nagendra; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Type 1 Diabetes Mellitus (T1D) is an autoimmune disorder marked by the destruction of insulin-producing pancreatic beta-cells. While insulin therapy remains the standard of care, advancements in immunotherapy present promising alternatives aimed at halting disease progression and reducing insulin dependence. This brief review highlights key immunomodulatory therapies, including teplizumab, which has demonstrated the ability to delay the onset of T1D, and rituximab, known for preserving beta-cell function, though its effects tend to be transient. Emerging treatments, such as stem-cell therapies, also show potential. However, significant challenges remain, including high costs, long-term safety concerns, and the need for personalized care. As this therapeutic landscape evolves, further research is critical to optimizing these strategies and moving closer to a potential cure for T1D. Keywords: Type 1 diabetes mellitus, autoimmunity, immunotherapy, anti-CD3 monoclonal antibody, teplizumab,